Efficient and Anisotropic Fog Harvesting on a Hybrid and Directional Surface. Issue 2 (5th December 2016) - Wu, Jinbo; Zhang, Lianbin; Wang, Yuchao; Wang, Peng
Abstract : A straight throughout superhydrophilic track that contains high contrast and directional wettability on a superhydrophobic surface is designed. Despite droplets that tend to slide more easily along a direction parallel to the track, it is found that such hybrid strip‐pattern surfaces have higher fog harvesting efficiency along a direction perpendicular to the tracks due to the larger accumulation area for droplet removal.